KARAKTER ANAK USIA DINI MELALUI KOMUNIKASI - Haraito Sihombing; Wiwin Komariah (IKIP Siliwangi, 2019)
Communication is done from birth, the baby communicates with the people around him through the sounds he heard, especially the sound of his mother seta face dilihanya. The role of early childhood educators as facilitators in the pattern of communication as an organist, as director, as moderator, as a guide, as observer. A study of family communication will determine the success rate of the process at school. Child and parent relationships are vertical relationships. The occurrence of miscommunication errors in language, not reading body language, not hearing the child's feelings, always commanding, comparing, violating, lying. Character building is influenced by how the communication and interaction that parents apply everyday. From the way it is applied, the children will learn in the future.